The effect of educational package on sexual function in cold temperament women of reproductive age - Nasim Baradaran-Akbarzadeh; Mahin Tafazoli; Morteza Mojahedi; Seyed Reza Mazlom (Wolters Kluwer Medknow Publications, 2018)
Introduction: Sexual health is one of the key factors to sustain marital life and having a good sexual function. On the other hand, temperament affects sexual function. Training is also one of the basic foundations for promoting sexual health. Therefore, the researcher has designed and implemented a study (2017) aimed "determining the study of educational package on sexual function in cold temperament women of reproductive age." Methods: This randomized clinical trial study was performed on 80 women in two groups (40 in each group). This study was done, in available method, on no pregnant women aged 20-40 years old that referred to health centers in Mashhad. DASS 21 sexual function and determining temperament questionnaires were completed in two groups before intervention. At first, the sexual function training package was held by the researcher at 6 sessions (twice a week for 3 weeks) that was based on nutrition, sport, and lifestyle axes. The control group also received routine care. A week after intervention finished, all the units completed a sexual function questionnaire. The results were analyzed by these techniques as SPSS software (version 16) and statistical tests such as Independent t-test, T-pair, Mann-Whitney, Chi-square, and Fisher's exact test. Results: At the beginning of the study, there was no statistically significant difference between the personal characteristics and the mean score of sexual function and all its dimensions in the two groups. The mean sexual performance score and all its dimensions after intervention were significantly different in intervention and control groups P < 0.001. Sexual function and all its dimensions were improved after intervention in the intervention group. Conclusion: Giving sexual function package has improved the sexual function of cold temperament women. So, for routine caring of cold temperament women, it is better that health center employees consider this training package as an effective, easy, available, nonpharmacological, and economic intervention.